Alternative shaper: a model for automatic design generation - Santos, F.; Kwiecinski, K.; de Almeida, A.; Eloy, S.; Taborda, B. (Formal Aspects of Computing, 2018)
This paper discusses the formalization of Alternative Shaper, a Spatial Grammar supplemented with procedural knowledge for supporting design generation. The nondeterministic process style perspective supports an exploratory and flexible specification of designs and the use of predicates relating shapes allow the confirmation of shape spatial restrictions on design processes. Although simple at this stage, Alternative Shaper actually offers interesting potentialities on design generation that may be improved soon with convenient abstractions.